Autogenous and engineered healing mechanisms of carbonated steel slag aggregate in concrete. (15th March 2016) - Pang, Bo; Zhou, Zonghui; Hou, Pengkun; Du, Peng; Zhang, Lina; Xu, Hongxin
Highlights: CSA is used as autogenous healing material in concrete. The investigation on repeated fracturing and healing. The composition and morphology of healing products are investigated. The ultrasonic test was used to analyze the cracks and healing condition of specimens. Abstract: The application of self-healing technology in concrete materials was widely investigated in the past decade. Although the micro-capsules and bacteria were considered as promising self-healing agents to realize durability enhancement of concrete, the high cost of micro-capsules and limited bacteria types are still big challenges that limit the widely application of this technology. As a result, it is necessary to develop cost-effective and environmentally friendly materials as self-healing agent in concrete. In this study, carbonated steel slag was used as aggregate to realize the autogenous healing of concrete. The self-healing performance of this concrete was investigated by comparing with the concretes prepared with normal aggregates and crushed steel slag aggregates. In addition, the hydration heat, X-ray diffraction, and scanning electron microscopy/energy dispersive spectroscopy results were analyzed to elucidate the self-healing mechanisms of concrete via using carbonated steel slag as healing agent. It was found that the healing products are mainly composed of CaCO3, Ca(OH)2, calcium–silicate–hydrate, calcium–aluminate–ferrite hydrate as well as amorphous silica. The cracks of aggregate have been healed to a certain extent that maximum healing width is about 20 μm and maximum healing length is about 5 mm.